Intertextual Relation For The Creation Of Fashion Contents - Iahn, Roberta Cesarino; Nascimento, Rodney (The Turkish Online Journal of Design Art and Communication, 2012)
The objective of this study is to highlight the interference of information technology for the fashion creation. Fashion is no longer a content specific of designers or expert journalists, being resistant to the language reduction system (Barthes, 2005). The technological interference in the image of fashion allowed a broad interchange of signs orchestrated by different people and backgrounds. Digital photography and blogs expanded relations between fashion (creation and content) and street trends (authorial consumption) where idea and experience assume a creative value of market (Future Concept Lab). This intertextual relation between fashion creation and information of its contents has established a network of associations from which it feeds an aesthetic system that changes the issue of authorship (creation) and property (information). Fashion creation and production are in web pages in order to allow a creative movement out of ateliers and fashion publishing to democratize the structure of a very elitist market until then. The fashion world designed by good designers and described by powerful editors (Matharu, 2011) has received new participants that have brought different perceptions on culture, aesthetics, and identity. Major corporate brands need to interact with an opinion production and content that are out of the industrial axis and market – at the same time independent and free to provide feedback and set new standards of value. Thus, we understand that the conflict is set between the new content production model related to the old-fashioned system of fashion production. We will try to clarify this issue from this paper.
Keywords: Fashion; Blogs; Digital photography; Creation; Moda; Bloglar; Difital fotoğrafçılık; Yaratıcılık